Dragonflies and Damselflies (Insecta: Odonata) - Seth Bybee (EDIS, 2005)
The order Odonata contains the dragonflies and damselflies and is one of the most popular insect groups. Odonates are popular with both the amateur and professional because they are large, colorful, easily observable and have exceptionally charismatic behaviors. In recent years dragonflies in particular have been popular with birders as many dragonflies rival birds in wingspan, color, gregariousness, and predictability. As a result of their popularity with the public, they have become the focus of many conservation efforts in North America, Europe, and Asia. This document is EENY-355, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date August 2005.